A Pioneer of Hands-On Education - Ledbetter, Mary Lee S. (American Society for Cell Biology, 2013)
This biography of the physicist and science educator Frank Oppenheimer uses his crowning achievement, San Francisco's Exploratorium, as the lens through which to explore his life and work.